Self‐assembled silane monolayers: an efficient step‐by‐step recipe for high‐quality, low energy surfaces. (May 2015) - Lessel, M.; Bäumchen, O.; Klos, M.; Hähl, H.; Fetzer, R.; Paulus, M.; Seemann, R.; Jacobs, K.
<x xml:space="preserve">Abstract</x> Organosilane self‐assembled monolayers (SAMs) are commonly used for modifying a wide range of substrates. Depending on the end group, highly hydrophobic or hydrophilic surfaces can be achieved. Silanization bases on the adsorption, self‐assembly and covalent binding of silane molecules onto surfaces and results in a densely packed, SAM. Following wet chemical routines, the quality of the monolayer is often variable and, therefore, unsatisfactory. The process of self‐assembly is not only affected by the chemicals involved and their purity but is also extremely sensitive to ambient parameters such as humidity or temperature and to contaminants. Here, a reliable and efficient wet‐chemical recipe is presented for the preparation of ultra‐smooth, highly ordered alkyl‐terminated silane SAMs on Si wafers. The resulting surfaces are characterized by means of atomic force microscopy, X‐ray reflectometry and contact angle measurements. Copyright © 2015 John Wiley & Sons, Ltd.